Effect of Covid-19 in Nepalese Tourism Sector and its Potential Measures in Nepal - Timsina, Tirtha Raj (Tribhuvan University Journal, 2021)
Tourism is a service-based industry with multiplicity of inter-linkages to the various other sectors in an economy. It contributes the significant amount of Gross Domestic Product (GDP) with remarkable employment opportunities in many countries of the world. This research work is conducted to identify the effect of corona virus disease 2019 (COVID-19) in Nepalese tourism industry and potential measure to cope with the effect in the economy by which necessary suggestions would recommend for this sector. This is a qualitative research based on the qualitative data gathered from primary as well as secondary sources. Fifteen respondents from different parts of Kathmandu valley have been purposively selected to obtain the first-hand responses who are formally engaged in tourism sector. It is found that there is significant effect in entire tourism sector and considerable decline globally and even the final statistics has not been measured yet. Nepal is also in the similar stream. Still there are lots of possibilities to cope with and develop new paradigm by handling the same things differently. This study concludes that there are plenty of measures to handle the problem created by the pandemic like COVID-19 throughout the economy including tourism. The knowledge acquired and lesson learned from the experiences make everything possible to handle it wisely so as to produce expected outcome that is why there is the enough sphere to revive Nepalese tourism in days to come.